The Effectiveness of Online Learning During the Covid-19 Pandemic at IPDN Campus NTB - Syaefullah; Agussalim Mad Arab; Mujahidin (Institute of Computer Science (IOCS), 2020)
The dynamics of adapting to new habits during the COVID-19 pandemic have had a major impact on various fields, especially in the field of education. Adjustment of adaptation to online learning is a priority policy in adapting to a new life. The Institute of Domestic Administration, West Nusa Tenggara Campus, which initially carried out direct face-to-face lectures, shifted to the use of online media and distance learning as a strategic step that must be taken to prevent the transmission of the Covid-19 virus. The purpose of this study was to know the effectiveness of online learning during the COVID-19 pandemic at IPDN NTB Campus. Methods The research uses a quantitative model with closed and open survey methods. Respondents from this study amounted to 392 Praja/students. The results of this study indicate that 50% of Praja/students want partly online learning (online), 24% want online learning, and 26% want face-to-face learning, so it can be concluded that online learning during the COVID-19 pandemic was quite effectively implemented.